Supply chain problem at PT.Campina Ice Cream Industry Surabaya - Tommy Minggus; Ananda Dwi Lestari; Firman Ardiansyah (AIBPM Publisher, 2018)
A business must involve many parties such as suppliers, companies, retailers, and customers. The parties form a network of supply chain. The development of the business world from time to time feels more competitive. Every company is always trying to survive in the flow of business competition. Therefore every company does supply chain management. Supply chain needs to be managed to maintain the business continuity so that strategy is needed. This study aims to examine the supply chain, strategy, and its application to the company PT Campina Ice Cream Industry as a manufacturing company and local company that has been known since its establishment in 1972 with a large production capacity. Ice Cream Campina product from PT Campina Ice Cream Industry has also managed to penetrate a large market share is evidenced by the distribution of Ice Cream Campina has reached the entire territory of Indonesia. But PT Campina Ice Cream Industry is experiencing problems regarding supply chain management that is in the process of production and distribution, one of which difficulties to expand distribution in the availability of electrification in the region. Because ice cream marketing requires electrical power for the cooling machine. Currently, the company still relies on one factory in Surabaya with an installed capacity of 30 million liters per year. The method to be used is descriptive method to solve supply chain problem from PT Campina Ice Cream Industry that is by formulating problem solving pattern that exist at present and future, based on data collected to be compiled, explained and analyzed. So that will provide solutions to increase the potential production and distribution in supply chain management from PT Campina Ice Cream Industry. Keywords : Supply Chain, Ice Cream, Manufactur, Electrification,Descriptive Method